Impact of COVID-19 on the Nature of Academic Work in Colleges of Education in Ghana - Adzaku, Sally Diviner Yaa; Adzakpa, Hayford Daniel (Technium Social Sciences Journal, 2022)
This study investigated the impact of COVID-19 on the nature of academic work in Colleges of Education in Ghana. The study adopted the descriptive survey design. A sample of 346 students was selected for the study. The participants chosen from the Evangelical Presbyterian College of Education, Peki College of Education and the St. Theresah College of Education in the Volta Region of Ghana through purposive, convenience and snowball sampling procedures. Data were gathered using an online questionnaire. Data were received from 270 students resulting in a 78% return rate. The data were analysed using frequencies and percentages as well as means and standard deviations. The results showed that tutors in Colleges of Education mostly taught during the COVID-19 period by sending audio recordings, texts or slide presentations to students. This was however not done in real time. Also, the tutors gave assignments and quizzes and gave feedback on the performance of the students. Finally, it was found that most students’ services were not provided satisfactorily when school came to an abrupt end because of the COVID-19 Pandemic. Specifically, student counselling services, student affairs services, organisation of tutorials/seminars and practical classes as well as technical support or IT services and supervisions and mentorships were not satisfactorily provided. It was therefore recommended that authorities in Colleges of Education should liaise with officers in charge of specific services like counselling, student affairs and technical or IT support so that they can effectively and satisfactorily assist students even when they are not on campus.